Psikologi Moral dan Usaha Mencari Pemimpin Politik yang Demokratis - Indro Adinugroho (Buletin Psikologi, 2016)
As a young democratic country, Indonesia needs various studies and experiences related to implementation of healthy democracy. Referring to psychological principle, decade long experience living in the Dark Age (new order regime) could become a nightmare or even traumatic experience for many Indonesia ns. In the context of Indonesia as a state, the traumatic event is not just experienced by individual, but also groups, organizations and civil society. Therefore, Indonesia needs numerous empirical supports to enhance its democratic condition. Moral psychology is considered as the empirical aspect that suitable in analyzing various political and democracy issues in Indonesia. Moral psychology is focusing its studies on human judgment related to right (correct) and w rong (false). This study is truly become empirical donation as an attempt to search political leader w ith democratic leadership as the trait. Comprehensive study in moral psychology could provide clear explanation for many political issues and also helping citizens to decide their political action for Indonesia